2022
DOI: 10.1093/gastro/goad066
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling mitophagy-mediated molecular heterogeneity and development of a risk signature model for colorectal cancer by integrated scRNA-seq and bulk RNA-seq analysis

Han Gao,
Qi Zou,
Linyun Ma
et al.

Abstract: Background Accumulating researchers have recognized mitophagy as a key player in tumors, but few studies have investigated its role in the tumor microenvironment (TME). Advances in the technology of single-cell RNA sequencing (scRNA-seq) have allowed unveiling the concealed features of the TME at cellular resolution. This study aimed to elucidate the role of mitophagy within the TME of colorectal cancer (CRC) and to establish a mitophagy-mediated risk model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…CRC exhibits significant heterogeneity in clinicopathological and molecular profiles, influencing tumor progression and treatment responses [ 21 ]. TME interactions facilitate CRC progression via multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…CRC exhibits significant heterogeneity in clinicopathological and molecular profiles, influencing tumor progression and treatment responses [ 21 ]. TME interactions facilitate CRC progression via multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Applying advanced next‐generation sequencing techniques, single‐cell RNA sequencing (scRNA‐Seq) enables the exploration of gene expression patterns in individual cells, unveiling the diversity within cell populations 15 . ScRNA‐seq has been used to characterize CRC heterogeneity to develop a risk model for cancer based on mitochondrial autophagy‐mediated profiling 16 . Also, Xu et al.…”
Section: Introductionmentioning
confidence: 99%
“…15 ScRNA-seq has been used to characterize CRC heterogeneity to develop a risk model for cancer based on mitochondrial autophagymediated profiling. 16 Also, Xu et al used scRNA-seq and observed a marked decrease in activated B cells in CRC with LM. 17…”
mentioning
confidence: 99%